Objective evaluation of total hip replacement in 127 dogs utilizing force plate analysis - Braden, T. D.; Olivier, N. B.; Blaiset, M. A.; Averill, S. M.; Bolliger, C.; DeCamp, C. E. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
Clinical evaluation of total hip replacement surgery has varied from a low of 30% to a high of 91.2% of return to good or excellent function. The goal of the project reported hereafter, was to obtain an objective evaluation, via the force plate analysis of a large number of dogs receiving total hip replacement as treatment for spontaneous coxarthrosis. Every surgical candidate was trotted across a force plate before replacement surgery and at an average of six months post-operative. The results were obtained from 127 dogs. For the entire group of dogs, the Zp (vertical peak force) improved 0.394 (10−2 N/kg) or 10.6%. The Zi (vertical impulse) improved an average of 13.6%. The improvements in Zp and Zi were statistically significant (p < 0.001).
Keywords: Total hip replacement; objective evaluation